Subtalar instability - Chin Yik Tan; Gowreeson Thevendran (Journal of Orthopaedic Surgery, 2023)
Subtalar instability is a confusing yet important condition in patients with lateral ankle instability. The author will explore subtalar kinematics, and how they are closely related to the joint stability of the subtalar joint, both with respect to its intrinsic ligaments and its extrinsic ligaments. As subtalar instability is difficult to diagnose, this article will provide readers with a better understanding of its clinical presentation. Discussions will also include useful radiographic modalities and the most recent evidence regarding their accuracy. The last section discusses surgical options and what the readers need to know in order to make a decision.